The Effectivenes of Speed Reading Technique in Narrative Text to Improve Students’ Reading Ability - Yuyun Ruqiyyat Said; Puteri Naflah Tabitah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study discusses whether teaching students at Muhammadiyah Boarding School Palopo's ninth grade how to read faster while reading narrative texts. The purpose of this study is to determine whether teaching students at Muhammadiyah Boarding School Palopo how to read quickly will improve their reading skills. This study employed classroom action research (CAR), which was divided into two meetings per cycle. There were 16 ninth-grade participants in the study. Tests and observation sheets were the research instrument. IBM SPPS 20 was used to evaluate the data. Planning, action, observation, and reflection were the four techniques used in this study's two cycles. The result of this research suggests that, students in Muhammadiyah Boarding School Palopo's ninth grade can improve their reading skills by using speed reading techniques when reading narrative texts. The majority of the post-test II results were better than the pre-test. The results of the students' pre-test can be used to demonstrate this. With an average score of 49.37, none of the students achieved the minimal completeness standard (KKM). Meanwhile, in the first cycle, two students achieved the minimum completeness criteria (KKM) with an average score of 65.62. In the test second cycle, 16 students reached the minimum completeness criteria (KKM) and exceeded the minimum completeness criteria with an average score of 89.37.